Low‐Grade Heat Harvesting: Efficient Low‐Grade Heat Harvesting Enabled by Tuning the Hydration Entropy in an Electrochemical System (Adv. Mater. 13/2021). Issue 13 (1st April 2021) - Gao, Caitian; Liu, Yezhou; Chen, Bingbing; Yun, Jeonghun; Feng, Erxi; Kim, Yeongae; Kim, Moobum; Choi, Ahreum; Lee, Hyun‐Wook; Lee, Seok Woo
Abstract : In article number 2004717, Seok Woo Lee and co‐workers present an efficient low‐grade heat‐harvesting system with a Carnot efficiency as high as 50%. By tuning the hydration entropy during the electrochemical reaction, the temperature coefficient reaches a high value in the thermally regenerative electrochemical cycle. Moreover, harvesting of thermal energy with various ranges, from 10 °C to 50 °C, is demonstrated for practical applications.